Historical dataset details the distribution, extent and form of lost Ostrea edulis reef ecosystems - Ruth H. Thurstan; Hannah McCormick; Joanne Preston; Elizabeth C. Ashton; Floris P. Bennema; Ana Bratoš Cetinić; Janet H. Brown; Tom C. Cameron; Fiz da Costa; David W. Donnan; Christine Ewers; Tomaso Fortibuoni; et al. (Scientific Data)
Abstract Ocean ecosystems have been subjected to anthropogenic influences for centuries, but the scale of past ecosystem changes is often unknown. For centuries, the European flat oyster (Ostrea edulis), an ecosystem engineer providing biogenic reef habitats, was a culturally and economically significant source of food and trade. These reef habitats are now functionally extinct, and almost no memory of where or at what scales this ecosystem once existed, or its past form, remains. The described datasets present qualitative and quantitative extracts from written records published between 1524 and 2022. These show: (1) locations of past flat oyster fisheries and/or oyster reef habitat described across its biogeographical range, with associated levels of confidence; (2) reported extent of past oyster reef habitats, and; (3) species associated with these habitats. These datasets will be of use to inform accelerating flat oyster restoration activities, to establish reference models for anchoring adaptive management of restoration action, and in contributing to global efforts to recover records on the hidden history of anthropogenic-driven ocean ecosystem degradation.